(untitled) (Ius Novum, 2025)
The article is an analysis of the amendment to article 296 § 4a of the penal code, as a result of which the circle of entities that may file a motion for prosecution of the offence of criminal mismanagement without harm has been broadened. Prior to the amendment, only the wronged party had such a right; now it is also available to a partner, shareholder or stockholder of the wronged company or member of the wronged cooperative. The purpose of this analysis was to assess whether, in fact, this amendment was necessary and whether its introduction complied with the principle of subsidiarity of criminal law. In the author’s opinion, there is no sufficient justification for this amendment and its introduction appears to be the result of a faulty identification of the reasons for the rare application of the provision sanctioning the offence of criminal harmless mismanagement, which the legislator identified in the excessively limited circle of persons who may file a motion for prosecution of this offence. Meanwhile, in fact, the lack of practical application of this provision lies in its construction, which significantly limits the range of facts that we can fit into its elements. Moreover, the introduced solution does not seem to be reconcilable with the principle of subsidiarity of criminal law, as it constitutes an excessive interference of criminal law in corporate relations, threatening the abuse of this institution.